The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1979
DOI: 10.3109/01485017908987304
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Estradiol-17/β on Reproduction in Adult Male Rats

Abstract: Estradiol-17p (E2-17p) treatment induced dose-related reduction of sperm population and eventual azoospermia, atrophy of accessory organs, and suppressed serum LH and testosterone levels. In spite of all these alterations mating behavior was not affected, although the number of implantation sites paralleled the reduction of sperm population, suggesting that the primary detectable response to E2-17P treatment is related to the steroidogenic components of the testis and the hypothalamic pituitary axis. The durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
(4 reference statements)
1
3
0
Order By: Relevance
“…Moreover, complete degeneration of seminiferous tubules and depopulation of germinal cells occurred in testis of rats treated for 24 days which indicate that these effects are dependent on the duration of the treatment. Hunt et al (1979) also reported that the duration of treatment is more critical for the induction of azoospermia in the rat than the total dose of estradiol, in support of our present observations and earlier data (Rao and Chinoy, 1983). Thus, E2B manifested a direct effect on testicular steroidogenesis by inhibiting the Leydig cell function concomitant with an accumulation of protein and cholesterol and a reduction in the activities of 3ß-and 17ß-hvdroxysteroid dehydrogenases (HSDs) in steroidogenic organs in treated rats.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, complete degeneration of seminiferous tubules and depopulation of germinal cells occurred in testis of rats treated for 24 days which indicate that these effects are dependent on the duration of the treatment. Hunt et al (1979) also reported that the duration of treatment is more critical for the induction of azoospermia in the rat than the total dose of estradiol, in support of our present observations and earlier data (Rao and Chinoy, 1983). Thus, E2B manifested a direct effect on testicular steroidogenesis by inhibiting the Leydig cell function concomitant with an accumulation of protein and cholesterol and a reduction in the activities of 3ß-and 17ß-hvdroxysteroid dehydrogenases (HSDs) in steroidogenic organs in treated rats.…”
Section: Discussionsupporting
confidence: 93%
“…The suppression of 17x-hydroxylass and 17-20 desmolase activities by estrogens in testis of laboratory animals and human being have also been extensively reviewed (Dörner et al, 1975;Steinberger et al, 1977;Dufau et al, 1978). The loss of ofgan weights, significant decrease in androgenic parameters of target organs and in sperm population, loss of their motility as well as increase in abnormal spermatozoa in epididymis leading to 100% failure in fertility have also been reported as a consequence of androgen deprivation in treated rats (Hunt et al, 1979;Chinoy M. R. et al, 1984;Bao and Chinoy, 1983). However, there is a paucity of reports on the effects of estrogens on the histoarchitecture and functional integrity of reproductive tract in male rats.…”
Section: Introductionmentioning
confidence: 99%
“…Testicular steroids exert a feedback action on the hypothalamus and pituitary gland to regulate gonadotrophin secretion in young (Schanbacher, 1980a) and mature rams (Schanbacher, 19806). Oestrogen-induced testicular atrophy in mature rats is considered to be secondary to inhibition of LH secretion (Swerdloff & Walsh, 1973;Verjan, de Jong, Cooke, van der Molen & Eik-Nes, 1974;de Jong, Uilenbroek & van der Molen, 1975;Hunt, Saksena & Chang, 1979). Thus, the influence of oestradiol-17ß treatment on sexual development in bulls appeared to be worthy of study.…”
Section: Introductionmentioning
confidence: 90%
“…In-vitro studies have suggested that the drug has a direct effect on testicular steroidogenesis (Barbieri et al, 1977). Oestrogens also have anti-androgenic properties in the male, causing azoospermia and reduction of plasma testosterone levels (Verjans, de Jong, Cooke, van der Molen & Eik-Nes, 1974;Bartke, Williams & Dalterio, 1977;Hunt, Saksena & Chang, 1979). The present study describes the effect of danazol and oestradiol-17ß on the histochemistry of the testis and epididymis of the gerbil.…”
Section: Introductionmentioning
confidence: 81%